Improving nitrogen retention of cattle slurry with oxidized biochar: An incubation study with three different soils. Issue 1 (11th November 2022) - Cao, Xinyue; Reichel, Rüdiger; Wissel, Holger; Brüggemann, Nicolas
Abstract: The application of livestock slurry in soils can lead to nitrogen (N) losses through ammonia (NH3 ) emission or nitrate (NO3 − ) leaching. Oxidized biochar has great potential to mitigate N losses due to its strong adsorption capacity; however, the effects of oxidized biochar in different soils treated with slurry are currently unclear. Here, we investigated the effect of untreated and oxidized biochar (applied at a rate of 50 kg C m −3 slurry) on reducing N losses in a laboratory experiment with three different soils (loamy sand, sandy loam, loam) amended with cattle slurry at an application rate of 73 kg N ha −1 . Oxidized biochar reduced NH3 emissions by 64–75% in all soils, whereas untreated biochar reduced NH3 emissions by 61% only in the loamy sand. Oxidized biochar significantly reduced the NO3 − content in the soil solution of the loamy sand in the early phase of the incubation and led to a significantly higher NO3 − concentration in the same soil compared with the slurry‐only treatment at the end of the experiment, indicating a significant increase in NO3 − retention in this organic C–poor soil. We conclude that oxidized biochar can reduce N losses, both in the form of NH3 emission and NO3 − leaching, from cattle slurry applied to soil, particularly in soil with soil organic carbon content <1% and pH <5 (i.e., oxidized biochar can serve as a means for improving the quality of marginal and acidic soils). Core Ideas: Application of livestock slurry to the soil can result in large nitrogen (N) losses. The addition of biochar to slurry can reduce the loss of N due to its properties. Oxidation can improve the N retention capacity of biochar. Oxidized biochar can reduce soil ammonia (NH3 ) emissions after slurry application. Oxidized biochar has the potential to improve the quality of marginal and acidic soils.